2010
DOI: 10.3892/or_00000831
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulated expression of matrix metalloproteinase-2 and transforming growth factor-β in melanoma development and progression

Abstract: Abstract. Previous studies have found that matrix metalloproteinase-2 (MMP-2) and transforming growth factor-ß (TGF-ß) can be considered as biomarkers and indices of disease progression in several human cancers. In this study, we investigated the plasma levels of MMP-2 and TGF-ß and their correlation in 49 primary cutaneous melanoma and 10 metastatic melanoma. Plasma MMP-2 and TGF-ß levels in patients with primary melanoma were significantly higher than those of healthy controls. These protein levels were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Malaponte et al (6) found that plasma levels of MMP-2 and TGF-β in patients with primary melanoma were significantly higher than those of healthy controls and those significantly higher levels were found in patients with metastatic melanoma. Extracellular factors, such as the inflammatory cytokine IL-1β has been implicated in facilitating inflammation and melanoma tumor growth (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malaponte et al (6) found that plasma levels of MMP-2 and TGF-β in patients with primary melanoma were significantly higher than those of healthy controls and those significantly higher levels were found in patients with metastatic melanoma. Extracellular factors, such as the inflammatory cytokine IL-1β has been implicated in facilitating inflammation and melanoma tumor growth (10).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have demonstrated that elevated levels of matrix metalloproteinases are associated with rapid progression of metastatic melanoma (5,6). MMP activity is regulated by and dependent upon environmental influences from surrounding stroma cells, ECM proteins, systemic hormones and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are a family of proteinases with various substrates and functions, including angiogenesis, tissue invasion, inflammation, and tumor metastasis (HadlerOlsen et al, 2010;Kessenbrock et al, 2010). In melanoma, both MMP-2 and MMP-9 were involved in cell invasion (van den Oord et al, 1997;Simonetti et al, 2002); however, only overexpression of MMP-2 is correlated with progression and survival (Vaisanen et al, 1998(Vaisanen et al, , 2008Orimoto et al, 2008;Malaponte et al, 2010). To our best knowledge, regulation of MMP-2 by Nox1 has not been reported in cancer cells including melanoma.…”
Section: Introductionmentioning
confidence: 98%
“…Since GLI2 is a critical substrate that is necessary for response of the hedgehog (HH) pathway, cross-talk between the TGF-beta and HH pathways may induce a positive feedback loop, promoting tumor progression and metastasis [46]. TGF-beta leads to MMP-2 upregulation in several cancers and expression of the two proteins has been found to be correlated in plasma from advanced melanoma patients [47]. Intravital imaging and microarray analysis of B16 melanoma tumors demonstrated that TGF-beta signaling can reverse features that are characteristics of differentiated melanocytes and increase cell motility [48].…”
Section: Tgf-betamentioning
confidence: 99%